The Effect of the Use of Wordwall Media on the Learning Outcomes of Grade 5 Students on IPAS Learning - Putri, Candra Avista; Hanifah, Nur Hidayah; Ningrum, Dian Eka Aprilia Fitria (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Science subjects that are often considered complicated and boring by some students require innovation in learning methods to optimize the achievement of student learning outcomes. The purpose of this study is to determine the influence of the use of wordwall media on student learning outcomes in elementary schools. The methodology of this research is quantitative, with a pre-experimental approach of design on group pretest postest. The subjects in this study are 21 5th grade students. The data collection techniques carried out are observation, interviews, and tests. Data analysis uses the Wilcoxon test as an alternative to the paired sample t-test which does not meet the requirements. The results of the Wilcoxon test in the statistical test showed that the acquisition of a sig value of 0.000 < 0.05 so that it can be stated that there is an influence of the use of wordwall media on student learning outcomes. This research provides recommendations for educators in elementary schools to take advantage of technology in accordance with the needs and developments of the times such as wordwalls that can be used as support during the learning process.